True Parthenogenesis and Female-Biased Sex Ratios in Cicadomorpha and Fulgoromorpha (Hemiptera, Auchenorrhyncha) - Dora Aguín-Pombo; Valentina G. Kuznetsova (Insects, 2023)
Insects are renowned for their remarkable diversity of reproductive modes. Among these, the largest non-holometabolous order, Hemiptera, stands out with one of the most diversified arrays of parthenogenesis modes observed among insects. Although there are extensive reviews on reproduction without fertilization in some hemipteran higher taxa, no such analysis has been conducted for the large suborders Fulgoromorpha (planthoppers) and Cicadomorpha (leafhoppers). In both groups, there are species that reproduce by true parthenogenesis, specifically thelytoky, and in Fulgoromorpha, there are species that reproduce by pseudogamy or, more specifically, sperm-dependent parthenogenesis. In this review paper, we give and discuss the only currently known examples of true parthenogenesis in Fulgoromorpha and Cicadomorpha, mainly from the planthopper family Delphacidae and the leafhopper family Cicadellidae. We analyze patterns of distribution, ecology, mating behavior, acoustic communication, and cytogenetic and genetic diversity of parthenoforms and discuss hypotheses about the origin of parthenogenesis in each case. We also highlight examples in which natural populations show a shift in sex ratio toward females and discuss possible causes of this phenomenon, primarily the influence of endosymbiotic bacteria capable of altering the reproductive strategies of the hosts. Our review is mainly based on studies in which the authors have participated.